Orbivirus NS4 Proteins Play Multiple Roles to Dampen Cellular Responses - Mohd Jaafar, Fauziah; Belhouchet, Mourad; Monsion, Baptiste; Bell-Sakyi, Lesley; Mertens, Peter P. C.; Attoui, Houssam (Viruses, 2023)
Non-structural protein 4 (NS4) of insect-borne and tick-borne orbiviruses is encoded by genome segment 9, from a secondary open reading frame. Though a protein dispensable for bluetongue virus (BTV) replication, it has been shown to counter the interferon response in cells infected with BTV or African horse sickness virus. We further explored the functional role(s) of NS4 proteins of BTV and the tick-borne Great Island virus (GIV). We show that NS4 of BTV or GIV helps an E3L deletion mutant of vaccinia virus to replicate efficiently in interferon-treated cells, further confirming the role of NS4 as an interferon antagonist. Our results indicate that ectopically expressed NS4 of BTV localised with caspase 3 within the nucleus and was found in a protein complex with active caspase 3 in a pull-down assay. Previous studies have shown that pro-apoptotic caspases (including caspase 3) suppress type I interferon response by cleaving mediators involved in interferon signalling. Our data suggest that orbivirus NS4 plays a role in modulating the apoptotic process and/or regulating the interferon response in mammalian cells, thus acting as a virulence factor in pathogenesis.